Optimization of long-term fracture conductivity with quartz: An experimental investigation - Wei, Jian-Guang; Wang, Xian-Jun; Fu, Xiao-Fei; Gong, Peng-Qi; Zhou, Xiao-Feng; Li, Yu-Wei; Yang, Ying; Chen, Ying-He; Jia, Bao; Wu, Jie (Frontiers in Energy Research, 2022)
For the purpose of cost management, many companies and research institutions have carried out technical research on the replacement of ceramic with quartz sand as proppant. However, few studies have systematically carried out short-term and long-term conductivity evaluation experiments for quartz sand proppants with different particle sizes. It is urgent to conduct experiments on the conductivity of quartz sand, and optimize the fracturing design based on the experimental results. The conductivity is the key indicator of the fracturing effect. The greater the conductivity, the better the hydraulic fracturing effect, and the longer the effective period, the higher the fracturing benefit. In this study, by evaluating the long-term conductivity of proppant, the influence of the type of quartz sand proppant, proppant particle size and sand paving concentration on the fracture conductivity are studied. Main results show that a) the proppant performance of quartz sand produced in Chifeng is better than that of produced in Tongliao; b) The long-term conductivity experiment results show that the conductivity of quartz sand proppant produced in CF is better than that of TL, and under the same sanding concentration and closing pressure, the larger the particle size of the quartz sand, the higher the conductivity, and the greater the decrease in conductivity with the increase of the closing pressure; c) In the influence of sand paving concentration, when the sand paving concentration is 5 kg/m2 and 7.5 kg/m2, the conductivity increase with the increase of the sand paving concentration.